ROZWIJANIE KOMPETENCJI MEDIALNEJ WŚRÓD PRZYSZŁYCH NAUCZYCIELI JĘZYKÓW OBCYCH W RAMACH PRACY W TANDEMIE ELEKTRONICZNYM. PROJEKT POLSKO-NIEMIECKI - Adamczak-Krysztofowicz, Sylwia; Szczepaniak-Kozak, Anna (Neofilolog, 2019)
Media literacy is one of the basic elements of a foreign language teacher’s workshop. Foreign language teaching recommends using media in the classroom not only because it facilitates learning and teaching, but also because it fosters learner autonomy, stimulates creativity and lowers the affective filter. Taking this into account, the authors consider how to develop the media competence of future teachers of English and German as foreign languages from both theoretical and practical perspectives. In the empirical part of the paper the authors present the aims, participants, stages and results of an e-tandem project that targeted a group of Polish and German students.